Kandungan Senyawa Bioaktif Teh Herbal Daun Kenikir (Cosmos caudatus Kunth.) pada Perlakuan Suhu Pengeringan dan Ukuran Partikel - Indriyani, Luh Kurnia Dwi; Wrasiati, Luh Putu; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): Maret, 2021)
K enikir is a plant easily found in Indonesia. Kenikir leaves contain high levels of antioxidants, phenols, flavonoids, and vitamin C that kenikir leaves can be used as tea. This study aims to determine the effect of drying temperature and particle size on the content of bioactive compound in kenikir herbal tea and to determine the right drying temperature and particle size in order to produce the best characteristics of kenikir herbal tea. This experiment used a group factorial randomized design with two factors. The first factor was drying temperature which consisted of 50 ± 2 °C, 60 ± 2 °C, and 70 ± 2 °C. The second factor was the particle size consisted of 40, 60, and 80 mesh. The variables observed in this study were total phenols, total flavonoids, vitamin C and antioxidants. T he data obtained were analyzed by analysis of variation (ANOVA) and analysis with real difference test ( tukey ) using Minitab 16 software. The results showed that the interaction between drying temperature and particle size had a very significant effect on total phenolics, total flavonoids, total vitamin C and antioxidant activity of kenikir herbal tea. The best treatment to produce kenikir leaf herbal tea was at a drying temperature of 70 ° C and a particle size of 80 mesh, with characteristics total phenol of 83.85 ± 0.12 mg GAE / g, total flavonoids of 7.25 ± 0.12 mg QAE / g, vitamin C 2.05 ± 027 mg / g and antioxidant activity (IC 50 ) of 157.87 ± 0.08 ppm . Keywords : bioaktives compound ,d rying temperature, kenikir herbal tea , size reduction